STRATEGI DINAS PERINDUSTRIAN DAN PERDAGANGAN DALAM PENINGKATAN DAYA SAING UKM DI KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Mohammad Arfandi Adnan (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to describe the strategy of the Department of Cooperatives and Cooperatives in empowering micro, small and medium enterprises (MSMEs) that focus on the trade sector. In empowering micro, small and medium enterprises, three phases are needed, namely initial, participatory and emancipatory. The research method used is descriptive qualitative, which is to provide an appropriate description or explanation objectively related to the actual situation of the object under study. The instruments of data collection are interviews and observations in locations and documents. The results of this study indicate that the Koperindag Department's empowerment strategy in empowering small, micro and medium enterprises is not optimal. Empowerment carried out by the government at an early stage is quite instrumental by providing training and counseling. The participatory phase of the community and the government has collaborated in developing MSMEs. While in the emancipatory phase the government is still constrained by the provision of facilities and infrastructure in the development of SMEs.